Assessing the concentration and potential health risk of heavy metals in China's main deciduous fruits - Ji-yun NIE; Li-xue KUANG; Zhi-xia LI; Wei-hua XU; Cheng WANG; Qiu-sheng CHEN; An LI; Xu-bo ZHAO; Han-zhong XIE; Duo-yong ZHAO; Yong-long WU; Yang CHENG (Journal of Integrative Agriculture)
To assess levels of contamination and human health risk, we analyzed the concentrations of the heavy metals lead (Pb), cadmium (Cd), chromium (Cr), and nickel (Ni) in China's main deciduous fruits — apple, pear, peach, grape, and jujube. The concentration order of the heavy metals was Ni>Cr>Pb>Cd. In 97.5% of the samples, heavy metal concentrations were within the maximum permissible limits. Among the fruits studied, the heavy metal concentrations in jujube and peach proved to be the highest, and those in grape proved to be the lowest. Only 2.2% of the samples were polluted by Ni, only 0.4% of the samples were polluted by Pb, and no samples were polluted by Cd or Cr. Compared with the other fruits, the combined heavy metal pollution was significantly higher (P<0.05) in peach and significantly lower (P<0.05) in grape. For the combined heavy metal pollution, 96.9% of the samples were at safe level, 2.32% at warning level, 0.65% at light level, and 0.13% at moderate level. In the fruits studied, the contribution of heavy metals to the daily intake rates (DIR) followed the order of Ni>Cr>Pb>Cd. The highest DIR came from apple, while the lowest DIR came from grape. For each of the heavy metals, the total DIR from five studied fruits corresponded to no more than 1.1% of the tolerable daily intake, indicating that no significant adverse health effects are expected from the heavy metals and the fruits studied. The target hazard quotients and the total target hazard quotients demonstrated that none of the analyzed heavy metals may pose risk to consumers through the fruits studied. The highest risk was posed by apple, followed in decreasing order by peach and pear, jujube, and grape. We suggest that the main deciduous fruits (apple, pear, peach, grape, and jujube) of China's main producing areas are safe to eat.